The Downside of Water Service Delivery in the Mnquma Local Municipality, South Africa - Nodipha, Chulumanco; Konyana, Samkele; Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
South Africa is a semi-arid nation with limited water resources. Municipalities are expected to play a major role in ensuring that there is an adequate water supply in the communities they are serving; however, a significant proportion of municipalities are failing to provide their residents with sufficient water service delivery. The purpose of this study was to empirically investigate the factors that contribute to the failure of water service delivery in the Mnquma Local Municipality. The study was qualitative nature and utilised semi-structured interviews to collect data, which was analysed using thematic analysis. The sample of the study comprised six municipal employees and six residents from different rural areas of the Mnquma Local Municipality. The study found that loadshedding, theft and vandalism, and sand-filled dams were factors that contributed to the failure of water service delivery. Some implications and recommendations are flagged.